3(x-2)+46=-2x

Simple and best practice solution for 3(x-2)+46=-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)+46=-2x equation:


Simplifying
3(x + -2) + 46 = -2x

Reorder the terms:
3(-2 + x) + 46 = -2x
(-2 * 3 + x * 3) + 46 = -2x
(-6 + 3x) + 46 = -2x

Reorder the terms:
-6 + 46 + 3x = -2x

Combine like terms: -6 + 46 = 40
40 + 3x = -2x

Solving
40 + 3x = -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
40 + 3x + 2x = -2x + 2x

Combine like terms: 3x + 2x = 5x
40 + 5x = -2x + 2x

Combine like terms: -2x + 2x = 0
40 + 5x = 0

Add '-40' to each side of the equation.
40 + -40 + 5x = 0 + -40

Combine like terms: 40 + -40 = 0
0 + 5x = 0 + -40
5x = 0 + -40

Combine like terms: 0 + -40 = -40
5x = -40

Divide each side by '5'.
x = -8

Simplifying
x = -8

See similar equations:

| k-263.48=-381.09 | | 9c-3c=-8 | | x-19.7=17.48 | | 2x+4(2x-5)=-110 | | 8-9(4-1)(3-4)= | | -4.095+b=18.665 | | 4x-10=180 | | z-81.6=-81.6 | | x+95=180 | | -3-4x=5x-3 | | 5=0-2x | | 0=a+27.98 | | 2w^2-4w+9=0 | | 4w-5=23 | | 3x+80+x=180 | | 29-19=2(x-2) | | x+82.7=63.5 | | 4+8n=4 | | 70a^2b+27ab-9b= | | G^2-14g+49=0 | | x+(-0.0025)=0.0024 | | t^2+-2t+15=0 | | q(q+19)=-34 | | 12x^2+24x=15 | | 0x=4 | | 7x-2y=18 | | 8x-4=18+5x | | -t^2+2t+15=0 | | 2x^2-3x+3=1 | | -t^2+2t+15=h(t) | | 0x^2+5x+3=0 | | -252=-5796 |

Equations solver categories